2002
DOI: 10.1056/nejmoa012604
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Outcomes of Reconstruction or Amputation after Leg-Threatening Injuries

Abstract: Patients with limbs at high risk for amputation can be advised that reconstruction typically results in two-year outcomes equivalent to those of amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
511
8
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 790 publications
(557 citation statements)
references
References 37 publications
14
511
8
10
Order By: Relevance
“…The psychosocial scores were 11.5 at 24 months, and 16.7 at 84 months [24]. Bosse, et al reported physical SIP scores of 10.1 and psychosocial SIP scores of 11.1 at 24 months for early amputations [5]. When comparing the results of this study to these earlier reports, the outcomes of delayed amputation for failed limb salvage surgery in this series are more comparable to early amputation.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…The psychosocial scores were 11.5 at 24 months, and 16.7 at 84 months [24]. Bosse, et al reported physical SIP scores of 10.1 and psychosocial SIP scores of 11.1 at 24 months for early amputations [5]. When comparing the results of this study to these earlier reports, the outcomes of delayed amputation for failed limb salvage surgery in this series are more comparable to early amputation.…”
Section: Discussionsupporting
confidence: 51%
“…These mean scores are substantially better than those reported by multiple authors for early amputation [5,8,24]. Akula, et al reported the mean physical scores for early amputation were 16.2, and 15.6 for the psychological SIP [1].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations